UNDERSTANDING THE INTERNATIONALISATION MOTIVATION AND FRANCHISING STRATEGY: A STUDY OF AN INDONESIAN STREET FOOD SME IN MALAYSIA - Fadhilla Khansa; Ramona Blanes; Zurina Mohaidin (Journal of Islamic, Social, Economics and Development, 2022)
This paper is the findings from a study that explores the internationalisation motivation and process, including models, the country selection and franchise strategy, as well as the critical success factors of Indonesian street food SME in Malaysia. The emergence of SMEs in developing countries is a contributing driver of economic development and employment. Malaysia as a neighbouring country has a very similar character of society and culture becomes the first country for an Indonesian business that wants to expand internationally. The purpose of this research is to provide a framework to create a clear understanding about the internationalisation motivation and franchising strategy of Indonesian street food SME in Malaysia. The data were collected from a single case study of Kebab Turki Baba Rafi, an Indonesian street food SME that has successfully expanded internationally to nine countries with more than 1200 outlets. The result shows that market seeking is the main motivation for Kebab Turki Baba Rafi in internationalising to Malaysia. The company adopts a network approach and chooses the franchise strategy as the entry mode strategy to Malaysia to minimise risks. The company has particular criteria in selecting the destination country for internationalisation and its master franchisee.